Metaheuristic algorithms for optimisation of infrared heating in thermoforming process. (1st January 2011) - Erchiqui, F.; Nahas, N.; Nourelfath, M.; Souli, M.
Thanks to the low cost and good formability of thermoplastic materials, thermoforming process is widely used in plastic processing. However, some problems remain to be solved, notably the non-uniform thickness distribution caused by uneven energy distribution in the plastic sheet during infrared heating. To overcome this problem, the energy intercepted and absorbed by the plastic sheet must be carefully optimised. In this study, two metaheuristic approaches [simulated annealing (SA) and genetic algorithms (GAs)] are used and compared for optimising the energy intercepted by the material sheet. Optimisation results obtained for three examples (solution quality, computing time, and convergence) were analysed.